2016
DOI: 10.1007/s11356-016-6348-3
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyl 126 exposure in L6 myotubes alters glucose metabolism: a pilot study

Abstract: Polychlorinated biphenyls (PCBs) are increasingly recognized as metabolic disruptors. Due to its mass, skeletal muscle is the major site of glucose disposal. While muscle mitochondrial dysfunction and oxidative stress have been shown to play a central role in metabolic disease development, no studies to date have investigated the effect of PCB exposure on muscle energy metabolism and oxidative stress. In this pilot study, we tested the effect of exposure to PCB126 in L6 myotubes (from 1 to 2500 nM for 24 h) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 58 publications
5
22
0
Order By: Relevance
“…Despite the growing body of evidence supporting the role of coplanar PCBs in the development of insulin resistance and type 2 diabetes, the effects of PCB exposure on the insulin sensitivity and energy metabolism of skeletal muscle has not been thoroughly investigated. Our group demonstrated that a 24hr-exposure of L6 skeletal muscle cells to PCB126 induced a 20% decrease in glucose uptake and glycolysis (Mauger, Nadeau, Caron, Chapados, & Aguer, 2016). This altered glucose metabolism in PCB126-treated L6 myotubes was consistent with another study showing decreased GLUT4 translocation and glucose uptake in muscle of rats exposed to a mixture of PCBs (Williams et al, 2013).…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Despite the growing body of evidence supporting the role of coplanar PCBs in the development of insulin resistance and type 2 diabetes, the effects of PCB exposure on the insulin sensitivity and energy metabolism of skeletal muscle has not been thoroughly investigated. Our group demonstrated that a 24hr-exposure of L6 skeletal muscle cells to PCB126 induced a 20% decrease in glucose uptake and glycolysis (Mauger, Nadeau, Caron, Chapados, & Aguer, 2016). This altered glucose metabolism in PCB126-treated L6 myotubes was consistent with another study showing decreased GLUT4 translocation and glucose uptake in muscle of rats exposed to a mixture of PCBs (Williams et al, 2013).…”
Section: Introductionsupporting
confidence: 88%
“…Exposure to PCB126 has been associated with the development of insulin resistance and mitochondrial dysfunction (Connell, Singh, & Chu, 1999;Kim et al, 2017;Mauger et al, 2016;Tremblay-Laganière et al, 2019;Wakabayashi & Karbowski, 2001). PCB126 is a lipophilic compound that increases inflammation in adipose tissue (Gadupudi, Gourronc, Ludewig, Robertson, & Klingelhutz, 2015;Gourronc, Robertson, & Klingelhutz, 2017), and increased adipose tissue inflammation is one potential cause of insulin resistance and mitochondrial dysfunction development in skeletal muscle (Bhatnagar et al, 2010;Hwang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations